The effects of resisted sprint vs. plyometric training on sprint performance and repeated sprint ability during the final weeks of the youth soccer season - Borges, J. H.; Conceicao, M. S.; Vechin, F. C.; Pascoal, E. H. F.; Silva, R. P.; Borin, J. P. (Science & Sports, 2016)
Introduction: Starter players experience a sprint speed drop of up to 4.3% at the end of the soccer season. Players must therefore perform specific types of training, such as resisted sprint (RS) and plyometric (PT) training, to avoid decrements and improve sprint performance. However, studies so far have neither tested the efficiency of RS or PT in improving sprint performance and the repeated sprint ability (RSA) of soccer players at the end of the season, or compared these training methods to discover which is more effective. The aims of this study were to verify and compare the effectiveness of seven-week RS and PT training in improving the sprint performance and RSA of young soccer players at the end of the season. Summary of facts and results: Twenty under-17 players participated in the study (16.6 ± 0.6 years; 68.7 ± 9.2 kg and 175.0 ± 7.1 cm). Players performed additionally to soccer training, RS (n = 9) or PT (n = 11) training twice a week. The RS consisted of 4 sprint exercises with sled loads (10-13% body mass), while the PT consisted of 4 jump exercises. Sprint times were assessed before and after the training period using a sprint (0-30 m) and RSA test. RS induced greater improvements in sprint time than PT, amounting to 0-30 m ([Cohen's d effect size {d} = 0.37] vs. [d = -0.17]; RSAbest [d = 0.73] vs. [d = -0.21] and RSAmean [d = 0.95] vs. [d = 0.16]), respectively. Conclusion: RS is slightly better than PT for avoiding decrements and improving sprint performance and RSA abilities at the end of the season.